Daily behavioral research on Sumatran Orangutan (Pongo abelii) mothers and offsprings at Suaq Balimbing Research Station, Gunung Leuser National Park, Aceh Province, Indonesia - Dalil Sutekad; Miftahul Jannah; Lenni Fitri; Fauziah Fauziah (Society for Indonesian Biodiversity, 2022)
Abstract. Sutekad D, Jannah M, Fitri L, Fauziah F. 2022. Daily behavioral research on Sumatran Orangutan (Pongo abelii) mothers and offsprings at Suaq Balimbing Research Station, Gunung Leuser National Park, Aceh Province, Indonesia. Biodiversitas 23: 5108-5121. Discovering the daily behavior of female orangutan mothers and their offspring can provide information for use as a recent reference in orangutan conservation action plans. This research aims to determine the daily behavioral patterns of mother and offspring Sumatran orangutans (Pongo abelii) at the Suaq Balimbing research station. This study was conducted between June 2019 and March 2020 and used focal animal sampling as the method. The method used consists of searching and daily behavioral logging. The results of the research showed that six orangutan mothers and offsprings (three mother-offspring pairs) showed different behavioral patterns. The distinction was felt in the distribution of time spent on activities. Eating, moving, resting, nesting, and social activity are all part of an orangutan's daily behavior. The proportion of time allocation used in the daily activities of female mother and Sumatran orangutan pairs (Pongo abelii) that is successfully observed in the Suaq Balimbing research station are eating (68.79%), resting (11.59%), moving (11.02%), nesting (1.11%), others (5.04%) and unknown (2.45%). Orangutans' diet plants in Suaq Balimbing consist of 30 species from 25 families, including the liana diet, plants consumed with the seeds, and plants consumed by the bark. According to the findings of this study, the behavior of a mother Sumatran orangutan, while it is with its offspring can be described.